PENGARUH KOMITMEN ORGANISASI, SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Pada Dinas Perindustrian, Perdagangan, Koperasi, dan UKM Kabupaten Dairi) - May Sartika Tarigan; Arthur Simanjuntak; Duma Rahel Situmorang (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
This study aims to examine and analyze the effect of Organizational Commitment, Government Internal Control System (SPIP), and Human Resource Competence on the Application of Accrual-Based Government Accounting Standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency, in accordance with Government Regulation (PP) Number 71 of 2010 concerning Accrual-Based Government Accounting Standards which must be implemented comprehensively starting in 2015. This study uses a sampling method that is saturated sample, and data processing using multiple linear regression, F test and t test. This study uses primary data from questionnaires distributed to respondents. The results of this study indicate that partially organizational commitment and the government's internal control system (SPIP) have a positive and significant effect on the Application of Accrual-Based Government Accounting Standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency, while the competence of human resources has no effect on application of accrual-based accounting standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency. Simultaneously Organizational Commitment, Government Internal Control System (SPIP), and Human Resource Competence have a positive and significant impact on the Implementation of Accrual-Based Government Accounting Standards at the Department of Industry, Trade, Cooperatives, and SMEs of Dairi Regency.